Fourth Annual Summer Research Summit on Health Equity Organized by the Center of Excellence in Health Equity, Training and Research, Baylor College of Medicine, Houston, Texas 77030, USA on May 20, 2021 - Aanand Naik; Abbhirami Rajagopal; Adam Floyd; Adriana Gil; Aisha Tepede; Aisha Koroma; Aisha Deslandes; Akua Graf; Alejandra Ruiz-Velasco; Alexa Reyna-Carrillo; Alexandra Alvarenga; Alexia Awoseyi; et al. (Global Health and Education Projects, Inc., 2021)
The fourth annual summer research summit organized by the Center of Excellence (COE) in Health Equity, Training and Research, Baylor College of Medicine (BCM) was held on May 20, 2021. The theme of this year's summit was 'Strengthening Our Commitment to Racial and Social Justice to Improve Public Health.' Given the ongoing pandemic, the summit was conducted virtually through digital platforms. This program was intended for both BCM and external audiences interested in advancing health equity, diversity and inclusion in healthcare among healthcare providers and trainees, biomedical scientists, social workers, nurses, individuals involved in talent acquisition and development such as hiring managers (HR professionals), supervisors, college and hospital affiliate leadership and administrators, as well as diversity and inclusion excellence practitioners. We had attendees from all regions of the United States, India, Pakistan and the Demographic Republic of the Congo. The content in this Book of Abstracts encapsulates a summary of the research efforts by the BCM COE scholars (which includes post-baccalaureate students, medical students, clinical fellows and junior faculty from BCM) as well as the external summit participants. The range of topics in this year's summit was quite diverse encompassing disparities in relation to maternal and child health (MCH), immigrant heath, cancers, vaccination uptakes and COVID-19 infections. Various solutions were ardently presented to address these disparities including community engagement and partnerships, improvement in health literacy and development of novel technologies and therapeutics. With this summit, BCM continues to build on its long history of educational outreach initiatives to promote diversity in medicine by focusing on programs aimed at increasing the number of diverse and highly qualified medical professionals ready to introduce effective and innovative approaches to reduce or eliminate health disparities. These programs will improve information resources, clinical education, curricula, research and cultural competence as they relate to minority health issues and social determinants of health. The summit received very positive response in terms of zealous participation and outstanding evaluations; and overall, it was a great success.   Copyright © 2021 Lopez et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.